Circulating microRNA-203 predicts prognosis and metastasis in human colorectal cancer. Issue 4 (23rd December 2015) - Hur, Keun; Toiyama, Yuji; Okugawa, Yoshinaga; Ide, Shozo; Imaoka, Hiroki; Boland, C Richard; Goel, Ajay
Abstract : Background and aims: Distant metastasis is a major cause of deaths in patients with colorectal cancer (CRC), which is partly due to lack of robust metastasis-predictive biomarkers. In spite of the important function of microRNA (miR)-203 in cancer metastasis, its clinical significance in CRC metastasis remains unknown. Here, we evaluated the potential role of serum miR-203 as a non-invasive biomarker for CRC metastasis. Methods: MiR-203 expression was quantified by quantitative reverse-transcription PCR in 58 pairs of primary CRC (pCRC) and corresponding matched liver metastasis (LM), as well as 186 serum and 154 matched tissue specimens from patients with CRC in cohort 1. Next, we performed validation of miR-203 levels in serum from 144 patients with CRC in an independent cohort (cohort 2). Mouse models of CRC-associated metastases were established to identify the source of circulating miR-203. Expression patterns of miR-203 in tissues were determined by in situ hybridisation. Results: MiR-203 expression was significantly upregulated in LM compared with matched pCRC tissues. Serum miR-203 levels were significantly upregulated in a stage-dependent manner, and high miR-203 expression was associated with poor survival in patients with CRC in both patient cohorts. Increased miR-203 levels in serum indicated high risk for poor prognosis (HR=2.1), as well as metastasis to lymph nodes (OR=2.5), liver (OR=6.2), peritoneum (OR=7.2) and distant organs (OR=4.4). Serum miR-203 levels were significantly higher in animals with liver or systemic metastasis compared with controls. Conclusions: High levels of serum miR-203 associate with poor survival and metastasis, suggesting it to be a promising non-invasive prognostic and metastasis-predictive biomarker in patients with CRC.